A bênção de Aarão: um estudo literário, histórico e teológico de Nm 6,22-27 - Feitosa, Hugo Chagas (2022)
The pericope of Num 6:22-27, and the Aaronite blessing, or priestly blessing is one of the rare texts within the Pentateuch that are not included in the literary genre of narratives or normative texts, being an example of lyrical poetry within the Bible . In it God commands Aaron and his sons to bless each Israelite with a blessing formula. In addition to a literary composition rich in figures of speech and stylistics, the text is a historical and archaeological source that raise interesting questions about the use of blessing formulas in ancient Israel and the writing of biblical texts. All these elements allow for a rich theological reflection that dialogues with the deepest human questions